Scandium(III) and Yttrium(III) Complexes of Hydroxysalicylic Acid Ligands - Turkel, Naciye; Aydin, Rahmiye; Ozer, Ulviye (Asian Journal of Chemistry, 2016)
Interactions of scandium(III) and yttrium(III) with 2,X-dihydroxybenzoic acids (2,X-DHBA, X = 4-6) (H3L) have been investigated in aqueous solution by potentiometric method at 25°C and at an ionic strength of 0.1 M (KNO3 for Sc(III) and NaClO4 for Y(III)). It has been observed that at low pH, the coordination of 2,X-DHBA ligands to Sc(III) occurs through salicylate sites; while Y(III) binds it only from carboxylate. In more basic media the hydrolytic equilibria lake place, either in 1 : 1 or in 1 : 2 mole ratios of Sc(III) or Y(III) : H3L systems. The stability constants of the formed Sc(LH)+, Sc(LH)(H2L), Y(H2L)2+, Y(H2L)2+ type complexes and their mono hydroxo complexes have been determined.